Problem Solving Based Counseling Guidance Model With Forward Chaining For Critical Thinking Abilities - khadijah, khairiyah; Syafriafdi, Non; Oktary, Dian (Educational Guidance and Counseling Development Journal, 2025)
Revolusi Industry 5 . 0 sue the world of education in learning Which not only focus on achievement objective, However Also 21st century skills are needed known as 4 Cs ( Crativity, Critical Thinking, Communication, Collaboration ) learners  Which cover communication , think k r i t i s ,  think  creative , And collaboration and problem solving .Wrong one of them the biggest in education moment now is the time increase   ability p e m e c h a n problems ( Problem Solving ) in critical thinking skills . Learners are expected to have the ability For handle problem And find solution This study aims to produce a guidance and counseling model product with problem solving techniques using forward chaning . The hope of this product can be used by counselors and BK teachers in solving student learning problems using applications so that 21st century skills known as 4C can be realized . The design of this study is a Research and Development model where the research model produces certain products and tests the effectiveness of the resulting product. The design used in this study is a 4-D model development research design (Four D Models). The 4-D stages of four steps: 1 Define, 2. Design, 3 Develop, 4. Disseminate.